Cytokines, synaptic plasticity and network dynamics: a matter of balance - Laura Bellingacci; Jacopo Canonichesi; Andrea Mancini; Lucilla Parnetti; Massimiliano Di Filippo (Neural Regeneration Research, 2023)
The modern view of the immune system as a sensitizing and modulating machinery of the central nervous system is now well recognized. However, the specific mechanisms underlying this fine crosstalk have yet to be fully disentangled. To control cognitive function and behavior, the two systems are engaged in a subtle interacting act. In this scenario, a dual action of pro-inflammatory cytokines in the modulation of brain network connections is emerging. Pro-inflammatory cytokines are indeed required to express physiological plasticity in the hippocampal network while being detrimental when over-expressed during uncontrolled inflammatory processes. In this dynamic equilibrium, synaptic functioning and the performance of neural networks are ensured by maintaining an appropriate balance between pro- and anti-inflammatory molecules in the central nervous system microenvironment.